Uniform metal nanostructures with long-range order via three-step hierarchical self-assembly - Erb, Denise J. (Sci Adv, 2015)
Large-scale nanopatterning is a major issue in nanoscience and nanotechnology, but conventional top-down approaches are challenging because of instrumentation and process complexity while often lacking the desired spatial resolution. We present a hierarchical bottom-up nanopatterning routine using exclusively self-assembly processes: By combining crystal surface reconstruction, microphase separation of copolymers, and selective metal diffusion, we produce monodisperse metal nanostructures in highly regular arrays covering areas of square centimeters. In situ grazing incidence small-angle x-ray scattering during Fe nanostructure formation evidences an outstanding structural order in the self-assembling system and hints at the possibility of sculpting nanostructures using external process parameters. Thus, we demonstrate that bottom-up nanopatterning is a competitive alternative to top-down routines, achieving comparable pattern regularity, feature size, and patterned areas with considerably reduced effort. Intriguing assets of the proposed fabrication approach include the option for in situ investigations during pattern formation, the possibility of customizing the nanostructure morphology, the capacity to pattern arbitrarily large areas with ultrahigh structure densities unachievable by top-down approaches, and the potential to address the nanostructures individually. Numerous applications of self-assembled nanostructure patterns can be envisioned, for example, in high-density magnetic data storage, in functional nanostructured materials for photonics or catalysis, or in surface plasmon resonance–based sensing.